Feasibility, functionality, and user experience with wearable technologies for acute exacerbation monitoring in patients with severe COPD - Iorio, Olivia C.; Coutu, Felix-Antoine; Malaeb, Dany; Ross, Bryan A. (Frontiers in Signal Processing, 2024)
The increasing interest in remote patient monitoring technologies in patients with chronic obstructive pulmonary disease (COPD) requires a phased and stepwise investigative approach, which includes high-risk clinical subgroups who stand to benefit most from such innovations. Methods: Patients aged>40 with spirometry-confirmed COPD presenting with a current acute exacerbation (ECOPD) were recruited from a tertiary centre Day Hospital in this prespecified feasibility study. Heart rate, respiratory rate, oxygen saturation, skin temperature, and daily activity and overnight sleep quality parameters were collected remotely by a wearable biometric wristband and ring for 21 consecutive days. 'Total ambulatory wear time' and 'percent of usable data' for eligible vital sign parameters were calculated. Correlation and agreement between cardiorespiratory vital sign data were performed using Spearman's correlation rho and the Bland-Altman test, respectively. User experience was measured with end-of-study System Usability Scale (SUS) questionnaires.Results: Nine participants (mean age 66.8±8.4yrs, 22% female, mean FEV1 1.4L (34.1% predicted), with 'severe' (56%) or 'very severe' (44%) COPD) experiencing a current ECOPD were included. Wear time was 94% (wristband) and 88.2% (ring) of the total ambulatory study period. Wristbandobtained data (every 1 minute, artefact-free) revealed 99.2% and 98.6% of all heart rate and temperature data, respectively, was usable, whereas only 17.6% of all respiratory rate data was usable. Ring-obtained data (every 5 minutes, 'average' and 'good' quality) revealed 84.5% of all heart rate data was usable. Cross-sectional analyses with nurse-obtained vital signs revealed correlation coefficients of 0.56 (p=0.11) and 0.81 (p=0.0086) for wristband-obtained and ring-obtained heart rate, respectively, and only 0.15 (p=0.74) for wristband-obtained respiratory rate, without evidence of systematic/proportional bias. Longitudinal heart rate and respiratory rate inter-device analyses demonstrated correlations of 0.86 (p<0.001) and 0.65 (p<0.001), respectively. Finally, end-of-study SUS scores were 86.4/100 (wristband) and 89.2/100 (ring).Older adults with severe/very severe COPD experiencing a current ECOPD were capable of autonomous physiological data collection/upload/transmission from their home environment over several weeks using sophisticated wearable biometric technology, with favourable user experiences. Cross-sectional and longitudinal comparative results call into question the paradigm of single sets of infrequent/interval vital sign checks as the current 'gold-standard' in frontline clinical practice.